Sosialisasi Dan Pelatihan Packaging Pada UMKM Di Kelurahan Blitar Untuk Meningkatkan Daya Jual Produk - Ardiansyah Putra; Ariyani Dewi Safitri; Clariska Oktania Mega Saputri; Della Aulia Riskha Arifinda; Haliza Nugraheni; Gideon Setyo Budi Witjaksono (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2023)
Packaging is one part of a product's marketing strategy in order to increase competitiveness. The socialization and packaging training held in the Blitar village aims to provide understanding and assist MSME in increasing the attractiveness and selling value of their products so that they can be accepted by consumers. The result of this packaging socialization and training activity is to provide insight into innovative, attractive and up to date packaging so that the products being sold look more attractive and different from similar products. For example, packaging using boxes can be added or combined with ribbons, logos, thank you labels or seal stickers on product packaging. After holding socialization activities and packaging training, it is hoped that it will provide benefits for MSME players in Blitar village to increase their innovation and creativity in choosing the right packaging for their products so that the products sold are able to compete in the market and increase consumer appeal.